Ontologias de domínio na interpretação de consultas a bancos de dados relacionais - Marins, Walquíria Fernandes (2015)
There is an huge amount of data and information stored digitally. Part of this amount of data is available for consultation by Web, however, a significant portion is hidden, due to its storage form, and can’t be recovered by traditional search engines. This makes users face a common and growing challenge to search and find specific information. This challenge is enhanced by the unpreparedness of users to formulate searches and the limitations inherent in research technologies, that because of syntactic differences, can’t find probably relevant data. Aiming to expand the possibilities of semantic interpretation of a query, this work proposes an approach to interpretation of queries in natural language to relational databases through the use of domain ontologies as a tool for their interpretation and semantic enrichment. With the implementation of the approach and its appreciation against a backdrop of queries without the semantic enrichment it is observed that the approach contributes satisfactorily to identify the user’s intention.